A hyperlink network analysis of citizen blogs in South Korean politics - Park, Han Woo (Javnost (Ljubljana), 2008)
Citizen participation may become more deeply integrated into political environments as digital communication technologies such as the Internet and mobile phone are increasingly embedded in everyday life during the coming decade. In the Asian context, there is already an important role for digital media in the political arena as participatory communication channels in high-tech countries, such as South Korea, as well as in technologically less developed countries like the Philippines. In particular, the political use of blogs has been increasing due to the possibility to publish material online quickly and to distribute content with other bloggers. Because of these characteristics, blogs are perceived as both personal and collaborative media.The relational aspects of blogs, however, have not been sufficiently explored. That is the objective of this article and, based on data collected in July and August 2005, two analyses are presented. First, we examine citizenblogs that politicians frequently visit. Second, we analyse the co-inlinks to citizen blogs and attempt to ascertain the relation between these co-inlinks and the inter-linkage patterns among citizens. The fi ndings indicate that the preferred target of politicians' blogs is more likely to be those blogs maintained by citizens who explicitly express a political stance. In addition, the co-inlinks from a politician's list of neighbours to citizen blogs is associated with the inter-linkage network structure.
Keywords: Južna Koreja; politiki; komuniciranje; communication; politične komunikacije; spletne strani; spletni dnevniki; blogi